PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, PENGETAHUAN PENGELOLA, KETERSEDIAAN SARANA PRASARANA, DAN PENGALAMAN KERJA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Opd Kota Pekanbaru) - Febby Syahrani; Edfan Darlis; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the influence of the application of government accounting standards no quality of local government financial statements, the influence of management knowledge on the quality of local government financial statements, the influence of infrastructure facilities on the quality of local government financial statements, and the influence of work experience on the quality of local government financial statements. This research is included in quantitative research. The sample is determined by purposive sampling technique and sample determination for each OPD using proportional method. The sample in this research is 120 employees. Data analysis using multiple linear regression with SPSS Version 21.00 software. The result of the research shows that the application of government accounting standard has a significant influence on the quality of local government financial report, the management knowledge has a significant influence on the quality of local government financial report, the infrastructure availability means a significant influence on the quality of local government financial report.Keywords :Application of Government Accounting Standards, Management Knowledge, Infrastructure Availability, Working Experience and Quality of Local Government Financial Statements.